2020
DOI: 10.25002/tji.2020.1347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunoglobulins, CD4/CD8 T Lymphocyte Ratio and Interleukin-6 in COVID-19 Patients

Abstract: Introduction: The outbreak of novel coronavirus COVID-19 infections that started in China late 2019 has spread rapidly and cases have been recorded worldwide. So, in this study, we sought clarification of the clinical characteristics and importance of changing the lymphocyte group, antibodies, CD markers, and interleukin-6 in the serum of COVID-19 patients, which may help to clarify the pathogen and develop new biomarkers. Material and Methods: Venous blood samples had been accumulated from patients before tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The researchers added that the frequency of different cell types might be influenced by several factors, including age, gender, sickness, and medications. According to research (Mao et al 2020;Saleh et al 2020), White WBC count and peripheral blood lymphocytes are normal or slightly decreased in the early stages of COVID-19 infection, when patients have no symptoms, but these markers may change as the disease progresses. In a study of 140 hospitalized patients diagnosed with COVID-19 based on CT scan results, Zhang et al found that the leukocyte count was within normal limits in 68.1% of patients diagnosed with COVID-19, which is increased in 12.3% of patients, and decreased in 19.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers added that the frequency of different cell types might be influenced by several factors, including age, gender, sickness, and medications. According to research (Mao et al 2020;Saleh et al 2020), White WBC count and peripheral blood lymphocytes are normal or slightly decreased in the early stages of COVID-19 infection, when patients have no symptoms, but these markers may change as the disease progresses. In a study of 140 hospitalized patients diagnosed with COVID-19 based on CT scan results, Zhang et al found that the leukocyte count was within normal limits in 68.1% of patients diagnosed with COVID-19, which is increased in 12.3% of patients, and decreased in 19.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cough, shortness of breath, and fever are the most prevalent medical signs (Huang et al 2020), as are gastrointestinal symptoms such as nausea, vomiting, abdominal pain, increased total serum bilirubin levels, and elevated liver enzymes like GOT and GPT (Huang et al 2020;Cheung et al 2020). The significance of numerous symptoms, comorbidities, inflammation, and hypercoagulability indicators in disease progression and mortality in COVID-19 patients is becoming clearer (Saleh et al 2020;Moghadasi et al 2021;Jalil et al 2020Jalil et al , 2021aDilfy et al 2020;Marofi et al 2021a;Widjaja et al 2021;Turki Jalil et al 2021;Sarjito et al 2021;Jalil 2020). Diabetes, one of the main causes of morbidity, has been found to have a high prevalence and is linked to adverse disease progression in COVID-19 (Li et al 2020a;Guo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Iraq reported nearly similar results, where the resistant rates for penicillin antibiotics including ticarcillin, piperacillin and minocycline and trimethoprim+ sulfamthoxazole were 76.7%, 81.0%, 91.0% and 93.5%, respectively (26). Also, Abdul-Wahid, (24,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) in Iraq reported similar results where the resistant rates for ceftazidime, cefepime, ciprofloxacin, pefloxacin, gentamicin and aztreonam (64.0%, 63.5%, 59.0%, 58.5%, 63.0% and 57.0%), respectively. While, the other study in Iraq by Alkazrage (27) reported the resistant rates for imipenem, meropenem and colistin (35.0%, 31.0% and 21.8%), respectively.…”
Section: Discussionmentioning
confidence: 71%